Rhizosphere microbial ecological characteristics of strawberry root rot - Zhang, Meilin; Kong, Zirong; Fu, Huijing; Shu, Xiaolong; Xue, Quanhong; Lai, Hangxian; Guo, Qiao (Frontiers in Microbiology, 2023)
Strawberry (Fragaria × ananassa Duch.) holds a preeminent position among small fruits globally due to its delectable fruits and significant economic value. However, strawberry cultivation is hampered by various plant diseases, hindering the sustainable development of the strawberry industry. The occurrence of plant diseases is closely linked to imbalance in rhizosphere microbial community structure. In the present study, a systematic analysis of the differences and correlations among nonculturable microorganisms, cultivable microbial communities, and soil nutrients in rhizosphere soil, root surface soil, and non-rhizosphere soil of healthy and diseased strawberry plants affected by root rot was conducted. The goal was to explore the relationship between strawberry root rot occurrence and rhizosphere microbial community structure. According to the results, strawberry root rot altered microbial community diversity, influenced fungal community composition in strawberry roots, reduced microbial interaction network stability, and enriched more endophytic-phytopathogenic bacteria and saprophytic bacteria. In addition, the number of bacteria isolated from the root surface soil of diseased plants was significantly higher than that of healthy plants. In summary, the diseased strawberry plants changed microbial community diversity, fungal species composition, and enriched functional microorganisms significantly, in addition to reshaping the microbial co-occurrence network. The results provide a theoretical basis for revealing the microecological mechanism of strawberry root rot and the ecological prevention and control of strawberry root rot from a microbial ecology perspective.